Granular Synthesis : Reset. - Biennale Venezia 2001 (Ostfildern-Ruit : Hatje Cantz Verlag, 2001)
Granular Synthesis are pioneers of the audio-visual media, who, for ten years now, have dedicated themselves to the fusion of sound and image and who have translated it into a coherent medium. As an essential part of their artistic practice, they develop relevant software. They compile hardware configurations that enable them to play video as an intuitive instrument. With their almost symphonic performances and installations Granular Synthesis build electronic emotion machines, which encircle the public, overwhelm, attack and affect the senses.
Granular Synthesis, La Biennale di Venezia, österreichischer Pavillon, 2001
Duits
Engels
Granular Synthesis : Reset, La Biennale di Venezia : pav. Oostenrijk. La Biennale di Venezia, 2001-06 t/m 2001-11
boek
Keywords: Granular Synthesis; Oostenrijk